2016
DOI: 10.1021/acs.jafc.6b02955
|View full text |Cite
|
Sign up to set email alerts
|

Orally Available Collagen Tripeptide: Enzymatic Stability, Intestinal Permeability, and Absorption of Gly-Pro-Hyp and Pro-Hyp

Abstract: Collagen-derived small peptides, such as Gly-Pro-Hyp (GPH) and Pro-Hyp (PH), play a role in various physiological functions. Although collagen degrades in the gastrointestinal tract randomly and easily, it is not readily cleaved into bioactive peptides. To increase the bioavailability of bioactive peptides, a collagen tripeptide (CTP) was prepared from fish scales by the digestion method using collagenase from nonpathogenic Bacillus bacteria. It was demonstrated that Hyp-containing peptides-GPH and PH-were bet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
60
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(69 citation statements)
references
References 30 publications
8
60
1
Order By: Relevance
“…Furthermore, the Caco-2 Papp values reported here are similar to the Papp values of other short chain peptides determined across Caco-2: (x 10 -6 cm.s -1 ): e.g. Ile-Phe, 2.4 [46], Thr-Vap-Pro-Ser-Leu, 6.9 [20], and Gly-Pro-His, 1.1 [22], as well as Gly-Sar itself, 9.2 [44]. In addition, the Papp values of Apical addition of C10 in the presence of Gly-Sar increased the Papp of both peptides to levels similar to those obtained in the absence of Gly-Sar in both Caco-2 monolayers and rat jejunal mucosae.…”
Section: The Relatively High Papp Values [ 3 H]-ipp and [ 3 H]-lkp Obsupporting
confidence: 85%
See 1 more Smart Citation
“…Furthermore, the Caco-2 Papp values reported here are similar to the Papp values of other short chain peptides determined across Caco-2: (x 10 -6 cm.s -1 ): e.g. Ile-Phe, 2.4 [46], Thr-Vap-Pro-Ser-Leu, 6.9 [20], and Gly-Pro-His, 1.1 [22], as well as Gly-Sar itself, 9.2 [44]. In addition, the Papp values of Apical addition of C10 in the presence of Gly-Sar increased the Papp of both peptides to levels similar to those obtained in the absence of Gly-Sar in both Caco-2 monolayers and rat jejunal mucosae.…”
Section: The Relatively High Papp Values [ 3 H]-ipp and [ 3 H]-lkp Obsupporting
confidence: 85%
“…A meta-analysis of 19 human trials indicated however, that a combination of IPP and VPP induced an overall decrease in SBP of ̴ 4 mm Hg over a minimum of 8 weeks following doses of 2 -10 mg peptide /day in a range of food products, a result that might be clinically significant [17]. Previously we have demonstrated that IPP and LKP are substrates for small intestinal epithelial cell uptake via the apical membrane-located intestinal Peptide Transporter 1 , PepT1(SLC15A1) in vitro [18], a high affinity pathway that can also be accessed by other food-derived peptides [19][20][21][22][23]. Involvement of PepT1 in mediating di-and tri-peptide transport is indicated by decreased small intestinal epithelial permeation in the presence of the PepT1 inhibitor, glycyl-sarcosine (Gly-Sar).…”
Section: Introductionmentioning
confidence: 99%
“…resistant to further digestion by proteases or peptidases; the di-and tripeptides (Pro-Hyp and Gly-Pro-Hyp) are stable in gastrointestinal fluid and rat plasma for short-term retention (Sontakke et al 2016). Additionally, collagen peptides are key ingredients in nutricosmetic products and supplementary health food because they can increase skin hydration and improve facial skin conditions (Inoue et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the bioavailability of peptides transported by PepT1 was higher than those transported through the paracellular route. PepT1 has also been described as the carrier of angiotensin converting enzyme (ACE) inhibitory peptides IPP and LKP, which were released from milk β-casein and fish/chicken muscle protein, respectively [ 111 ], as well as of other food bioactive peptides [ 101 , 112 , 113 , 114 , 115 , 116 ]. In addition to PepT1, other peptide carriers present in the basolateral membrane have been suggested to participate in the transport of hydrolysis-resistant small peptides into blood.…”
Section: Bioavailability Of Food Peptidesmentioning
confidence: 99%